Genome-wide association study identifies susceptibility loci for dengue shock syndrome at MICB and PLCE1 - Simmons, Cameron (2018)
Hypovolemic shock (dengue shock syndrome (DSS)) is the most common life-threatening complication of dengue. We conducted a genome-wide association study of 2,008 pediatric cases treated for DSS and 2,018 controls from Vietnam. Replication of the most significantly associated markers was carried out in an independent Vietnamese sample of 1,737 cases and 2,934 controls. SNPs at two loci showed genome-wide significant association with DSS. We identified a susceptibility locus at MICB (major histocompatibility complex (MHC) class I polypeptide-related sequence B), which was within the broad MHC region on chromosome 6 but outside the class I and class II HLA loci (rs3132468, P(meta) = 4.41 × 10(-11), per-allele odds ratio (OR) = 1.34 (95% confidence interval: 1.23-1.46)). We identified associated variants within PLCE1 (phospholipase C, epsilon 1) on chromosome 10 (rs3765524, P(meta) = 3.08 × 10(-10), per-allele OR = 0.80 (95% confidence interval: 0.75-0.86)). We identify two loci associated with susceptibility to DSS in people with dengue, suggesting possible mechanisms for this severe complication of dengue.